Iowa Birdline update, October 7, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for October 7, 1991. The highlights for the update include the sighting of a Groove-billed Ani. Also included are handwritten notes with sightings of Western Grebes, American White Pelicans, Chimney Swifts and six American Pipits. Epson - sheet feed/flatbed